Genetic Variations in Vesicoureteral Reflux Sequelae - David S. Hains (Pathogens, 2016)
Urinary tract infections (UTI) are a common condition in children. Vesicoureteral reflux (VUR) represents a common associated condition with childhood UTI. UTI susceptibility appears to have a genetic component based on family and UTI cohort studies. Targeted analysis of innate immune system genetic variations indicate that these variations are important in UTI susceptibility. In this overview, we discuss how current cohorts and genetic strategies can be implemented to discover new susceptibility loci in patients with UTI.